2021
DOI: 10.1177/2050313x211025920
|View full text |Cite
|
Sign up to set email alerts
|

Effect of negative pressure wound therapy for legs in complex wound diabetic patients: Therapeutic challenge and review

Abstract: Diabetic foot is one of the main chronic complications caused by diabetes mellitus and can lead to limb amputation. Among the various wound treatment options, negative pressure wound therapy is a treatment modality based on vacuum-sealed drainage and vacuum-assisted closure to create a localized controlled negative pressure environment. In this case report, the patient sought medical attention and underwent surgical debridement of the dorsum of the right foot. Upon worsening of the wound condition, the patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
(14 reference statements)
0
6
0
Order By: Relevance
“…It has become an advanced technique for treating various acute and chronic wounds, with simple operation, and low requirements for operating conditions, which can also be performed at the bedside. 15,16 Its mechanisms in promoting wound healing are as follows [17][18][19][20] (3) A relevant study has shown that appropriate negative pressure can promote the reopening of previously occluded micro vessels in the wound, forming new capillaries, which significantly improves local microcirculation. Moreover, negative pressure can also relieve tissue edema.…”
Section: Discussionmentioning
confidence: 99%
“…It has become an advanced technique for treating various acute and chronic wounds, with simple operation, and low requirements for operating conditions, which can also be performed at the bedside. 15,16 Its mechanisms in promoting wound healing are as follows [17][18][19][20] (3) A relevant study has shown that appropriate negative pressure can promote the reopening of previously occluded micro vessels in the wound, forming new capillaries, which significantly improves local microcirculation. Moreover, negative pressure can also relieve tissue edema.…”
Section: Discussionmentioning
confidence: 99%
“…Although the complications of the two groups were not statistically different, vacuum sealing drainage has a higher effectiveness rate than standard therapy, reduces the length of hospital stay and results in larger wound size reduction. As a preferred course of treatment for people with diabetic foot ulcers, vacuum sealing drainage is what we advise based on the findings 46–49 …”
Section: Discussionmentioning
confidence: 99%
“…As a preferred course of treatment for people with diabetic foot ulcers, vacuum sealing drainage is what we advise based on the findings. [46][47][48][49] Limitations of the meta-analysis were as follows: there could be an assortment bias because some of the examinations that were chosen for the meta-analysis were excluded. Despite this, the omitted examination did not meet the requirements for inclusion in the meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, negative pressure wound therapy (NPWT) is used for treatment in various injuries including chronic wounds 1 and acute trauma, 2 burns, 3 and its applications are diversifying. In the management of burn injuries NPWT can be used for various purposes, and each purpose involves careful consideration of equipment, sealing, pressure, timing, and duration of treatment.…”
mentioning
confidence: 99%